Cost-utility and budget impact analyses of significant fibrosis detection in individuals with metabolic syndrome or obesity in Thailand - Chayanis Kositamongkol; Pichaya Tantiyavarong; Alissa Ratanatawan; Pimsiri Sripongpun; Prawej Mahawithitwong; Prawat Kositamongkol; Surasak Saokaew; Pochamana Phisalprapa (PLoS ONE, 2026)
Introduction Evidence on screening for significant fibrosis in individuals with metabolic syndrome or obesity at risk of metabolic dysfunction-associated steatotic liver disease is limited in low- and middle-income countries. We conducted a cost-utility analysis and a 5-year budget impact analysis of 3 one-time screening strategies versus no screening in Thai adults with metabolic syndrome or obesity. Methods We built a lifetime economic model from a societal perspective to estimate quality-adjusted life years (QALYs) and costs. Strategies were: (1) Fibrosis-4 index (FIB-4) followed by transient elastography (TE), (2) Steatosis-Associated Fibrosis Estimator score followed by TE, and (3) TE alone. Inputs came from a literature review and primary data analysis. Costs and outcomes were discounted at 3% annually. Incremental cost-effectiveness ratios (ICERs) were compared with a willingness-to-pay threshold of 160,000 THB (4,619 USD) per QALY gained. One-way and probabilistic sensitivity analyses were undertaken, and a 5-year budget impact analysis was performed from the payer perspective. Results In metabolic syndrome, FIB-4 + TE yielded an ICER of 104,588 THB (3,019 USD) per QALY gained versus no screening. The Steatosis-Associated Fibrosis Estimator score plus TE yielded 128,274 THB (3,703 USD). Extended dominance identified FIB-4 + TE as the sole cost-effective strategy. In obesity, all strategies were cost-effective, with TE alone preferred. The transition from fibrosis stage F3 to F4 most influenced ICERs. The probability that FIB-4 + TE was cost-effective ranged from 59% to 78%. Estimated annual budget impact over 5 years ranged from 564 to 2,314 million THB (16.3–66.8 million USD). Conclusions One-time screening was not uniformly cost-effective. In metabolic syndrome, only FIB-4 + TE was cost-effective. In obesity, all strategies were cost-effective. Given non-robustness in the estimated cost-effectiveness and the substantial budget impact, implementation should balance expected health gains against affordability.